Eustachian Tube Dysfunction in Children With Unilateral Cleft Lip and Palate: Differences Between Ipsilateral and Contralateral Ears. (June 2020) - Hu, Allen; Shaffer, Amber D.; Jabbour, Noel
Objective: To evaluate Eustachian tube dysfunction in the ipsilateral and contralateral ears, in children with unilateral cleft lip and palate (UCLP). Design: Retrospective chart review. Setting: Tertiary care children's hospital. Patients: Seventy-four consecutive patients with UCLP born between 2005 and 2011 and treated at UPMC Children's Hospital of Pittsburgh Cleft-Craniofacial Center were included. Main Outcome Measures: Conductive hearing loss, tympanogram type, number of middle ear effusions, tympanostomy tubes, and complications. Hypothesis was formulated prior to data collection. Results: Conductive hearing loss was nearly twice as common in the ipsilateral ear (43.2%) compared with contralateral (23.0%; P = .001, McNemar test). There were no significant differences in the frequency of each type of tympanogram between the contralateral and ipsilateral ears. The proportions of ipsilateral (90.5%) and contralateral (91.9%) ears with effusion were not significantly different. The total number of tubes received was not significantly different between the 2 ears (median of 2 bilaterally). When combined, complications (retractions, perforations, and cholesteatomas) were significantly more common in the ipsilateral ear (29.7%) compared with the contralateral ear (18.9%; P = .039, McNemar test). Conclusion: In children with UCLP, there were significantly more instances of conductive hearing loss and complications on the cleft side compared to the noncleft side. This suggests that Eustachian tube dysfunction may indeed be more severe on the cleft side. Considering this information, clinicians may need to be especially observant of the ipsilateral ear.